Robust coherent control of solid-state spin qubits using anti-Stokes excitation - Jun-Feng Wang (Nature Portfolio, 2021)
Optically detected magnetic resonance of defect spins typically relies on Stokes excitation, in which the excitation energy is larger than that of the emitted photon. Here, the authors use the opposite regime of anti-Stokes excitation to detect Si vacancy spins in SiC, with a threefold improvement in signal contrast.